2014
DOI: 10.3855/jidc.4126
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of vanA vancomycin-resistant Enterococcus faecium in a hospital in Porto Alegre, South Brazil

Abstract: Introduction: In Porto Alegre (South Brazil), since the first VRE isolation in 2000 until the middle of the last decade, the epidemiology of enterococcal infections presented the peculiarity that, as opposed to other regions of the country, almost all VRE were E. faecalis. The aim of this study was to investigate the microbiological and epidemiological characteristics of a VRE outbreak that occurred between August 2010 and September 2011 in Porto Alegre, South Brazil. Methodology: Twenty-nine isolates from inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
(47 reference statements)
5
8
0
2
Order By: Relevance
“…The esp expression on the surface of E. faecium seems to play a role in adherence and biofilm formation [28]. This gene could have a great role in the exchanging genetic mobile elements and could also be implicated in the adaptation of these bacteria to the hospital environment [29,30].Remarkably, our vanA E. faecium isolates presented a multiresistance phenotype, being resistant, in addition to glycopeptides, to erythromycin, tetracycline, ciprofloxacin, ampicillin, kanamycin, streptomycin, pristinamycin, and trimethoprimsulfamethoxazole. In the case of resistance genes erm(B) and tet(M), it is interesting to mention that they have been previously detected in the same conjugative plasmid as the van(A) gene, which indicates that coselection processes might have happened [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The esp expression on the surface of E. faecium seems to play a role in adherence and biofilm formation [28]. This gene could have a great role in the exchanging genetic mobile elements and could also be implicated in the adaptation of these bacteria to the hospital environment [29,30].Remarkably, our vanA E. faecium isolates presented a multiresistance phenotype, being resistant, in addition to glycopeptides, to erythromycin, tetracycline, ciprofloxacin, ampicillin, kanamycin, streptomycin, pristinamycin, and trimethoprimsulfamethoxazole. In the case of resistance genes erm(B) and tet(M), it is interesting to mention that they have been previously detected in the same conjugative plasmid as the van(A) gene, which indicates that coselection processes might have happened [31].…”
Section: Discussionmentioning
confidence: 99%
“…The agents tested were the following (μg/disk): vancomycin (30), teicoplanin [14]. Detection of pristinamycin resistance (15) and high-level resistance to gentamicin (500), kanamycin (1,000), and streptomycin (500) was performed according to the Antibiogram Committee of the French Society for Microbiology [15].…”
Section: Antimicrobial Susceptibility Testing and Detection Of Resistmentioning
confidence: 99%
“…Another study conducted with 29 isolates from a hospital in Southern Brazil observed that all isolates were VREfm carrying vanA gene and were part of a main clone (Resende et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Enterococcus faecium to rapidly acquire mobile genetic elements associated to antimicrobial resistance is well-established (Gilmore et al, 2013;Cattoir and Giard, 2014;García-Solache et al, 2016). Vancomycin-resistant Enterococcus faecium (VREfm) has become increasingly common in some hospital settings and their clonal spread has been described worldwide (Freitas et al, 2016;Mahony et al, 2018), including Brazil (Alves et al, 2017;Resende et al, 2014;Sacramento et al, 2017). Most VREfm isolated from Brazilian hospitals belong to clonal complex 17 (CC-17), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A vancomicina é bactericida para a maioria das bactérias Gram positivas e bacteriostática contra Enterococcus, no entanto, não apresenta efeito para as bactérias Gram negativas e micobactérias (Guimarães, Momesso, Pupo, 2010;Merlo, 2013 (Zanella et al, 2003, Oliveira, Bettcher, 2010Terra, Da Silva, 2017). Posteriormente ao primeiro caso de VRE no Brasil diversos estudos foram publicados relatando a disseminação de VRE em hospitais brasileiros (Zanella et al, 1997;Zanella et al, 2003;Palazzo et al, 2011;Bastião et al, 2012;Resende et al, 2014;Da Silva et al, 2014;Campos et al, 2014;Correia et al, 2015). E se tratando de perfil de resistência à vancomicina o E. faecium apresenta uma maior resistência quando comparado ao E. faecalis A resistência bacteriana desenvolvida pelas bactérias Gram positivas contra a vancomicina se dá através do mecanismo de reprogramação e modificação da estrutura-alvo da droga na estrutura bacteriana, prejudicando a capacidade de ação da droga no sítio alvo.…”
Section: Enterococcus Resistente à Vancomicina (Vre)unclassified